Предмет: Алгебра,
автор: klimenkol21
Вычислить:
1) (2/3)⁻³ - 4⁻²
2)(-0,1)⁻³ - (-0,2)⁻³
3)-(-0,1)⁻⁴ + (-0,2)²
Ответы
Автор ответа:
0
1) (2/3)⁻³ - 4⁻²=27/8-1/16=54/16-1/16=53/16=3 5/16
2)(-0,1)⁻³ - (-0,2)⁻³=-1000+125=-875
3)-(-0,1)⁻⁴ + (-0,2)² =10000+0,04=10000,04
2)(-0,1)⁻³ - (-0,2)⁻³=-1000+125=-875
3)-(-0,1)⁻⁴ + (-0,2)² =10000+0,04=10000,04
Похожие вопросы
Предмет: Математика,
автор: kalimanovapolina73
Предмет: Биология,
автор: b22n6s7yk8
Предмет: Физика,
автор: ptitsachastya113
Предмет: Литература,
автор: elboeva12
Предмет: Алгебра,
автор: azazin1488